Beam-wave Interaction Analysis of X-band Gridless Reltron - Tripathi P.; Kumar A.; Shee S.; Dwivedi S.; Jain P.K. (My University, 2025)
In this work, particle in cell (PIC) simulation study has been performed to observe the operating characteristics of the highly efficient gridless-reltron in X-band. A 3D PIC code of gridless reltron is designed using CST microwave studio. The RF interaction structure of the Gridless-reltron is a well-known linac structure i.e. side-coupled cavity (SCC). In the reltron, three modes are excited named as 0–mode, π/2–mode and π–mode. The π/2–mode is selected as the operating mode because it is unstable and it grows in amplitude. PIC simulation predicts that the modeled gridless reltron with the beam current of 200 A and a total 250 kV as a tube voltage produces a microwave power of ~13 MW at 8.56 GHz with a pulse width of 3.2 µsec and efficiency of ~26%, in the presence of a relatively low guiding magnetic field of 0.40 T. © 2019 URSI. All rights reserved.